Edukasi Pencegahan Bullying pada Anak Usia Dini di TK Dina Dini Desa Rao-Rao Dolok - Harahap, Rani Astria Silvera; Nurhalimah Harahap; Era Mutiah; Silveri Rahmadani Pasaribu; Ermis Pasaribu (Lembaga Pengembangan Kinerja Dosen, 2026)
Abstract: Bullying among young children is a serious issue that requires attention because it can affect all aspects of a child’s development. Bullying behavior can manifest as physical, verbal, and social actions that are carried out intentionally and repeatedly. Given this, it is crucial to implement preventive measures through educational initiatives involving all stakeholders in the education system, particularly teachers and students. The goal is to enhance participants’ understanding and awareness of the importance of creating a safe, welcoming, and bullying-free school environment. This educational activity was conducted at Dina Dini Kindergarten in Rao-Rao Dolok Village, Sosa Subdistrict, Padang Lawas Regency. The participants consisted of teachers and students from Dina Dini Kindergarten in Rao-Rao Dolok Village. The results showed an increase in the knowledge and understanding of both teachers and students regarding the concept of bullying, the forms of bullying that occur among young children, the resulting impacts, and the preventive measures that can be implemented within the school environment.